A Modified LEACH Protocol for Increasing Lifetime of the Wireless Sensor Network - Ananda Kumar S.; Ilango P.; Dinesh Grover Harsh (Cybernetics and Information Technologies, 2016)
Many studies have been proposed on clustering protocols for various applications in Wireless Sensor Network (WSN). The main objective of the clustering algorithm is to minimize the energy consumption, deployment of nodes, latency, and fault tolerance in network. In short high reliability, robustness and scalability can be achieved. Clustering techniques are mainly used to extend the lifetime of wireless sensor network. The first and foremost clustering algorithm for wireless sensor network was Low Energy Adaptive Clustering Hierarchy (LEACH). As per LEACH, some Cluster Head (CH) may have more nodes, some other may have less nodes, which affects the network performance. The proposed method MaximuM-LEACH provides a solution by load balancing the number of nodes equally by fixing the average value N, so the life time of the network is increased.